Imagining Hydropower: Transnational Narratives and Realities of the Stiegler’s Gorge Project in Tanzania, 1960s–1980s - Minja, Emma Athanasio (Zamani: A Journal of African Historical Studies, 2024)
Hydropower development in the Global South has attracted several donor programmes for decades. How have such interventions shaped energy imaginations in Tanzania? Adopting a historical perspective and drawing on transnationalism and travelling frameworks, this article examines hydropower aid interventions and the dynamic shifts of specific actors and discourses in bilateral relations. The primary focus is on Norway, a leading actor in planning the Stiegler’s Gorge hydropower project in Tanzania’s Rufiji Basin in the 1970s to mid-1980s. It seeks to understand how, despite substantial aid support, the project failed to kick off in the face of the country’s post-independence drive for industrialisation. The study unravels a history of shifting and sometimes conflicting discourses, offering a richer and more nuanced understanding of the hydropower imagination and the role of Norway in planning hydropower development in Tanzania.